CGIAR Research Program on Fish - Plan of Work and Budget 2019 - CGIAR Research Program on Fish (CGIAR Research Program on Fish, 2019)
Plans and activities for 2019 are centrally focused on delivering key outcomes that increase the impacts of fish in agri-food systems. Recognizing the broader cross-CGIAR food systems perspective, further cross-CRP cooperation and foresight analyses will also give attention to determining key research gaps for the future and opportunities for increasing the research and development outcomes from the FISH CRP.